Item Psychometric Property of Marital Quality Scale of Javanese People Using Rasch Model - Farida Agus Setiawati; Rizki Nor Amelia; Siti Rohmah Nurhayati (Universitas Ahmad Dahlan, 2022)
The measurement of marital quality has been done in many countries including Indonesia. This article described the characteristics of the item parameter endorsement index and item fit model in the data as the results of measurement of marital quality of Javanese people. The 420 couples (N = 840) from Daerah Istimewa Yogyakarta, Solo, Banyumas, and Pekalongan involved this research. The data collected were analyzed using the Rasch model with the Quest program. In general, the endorsement index moves higher as the category increases, and there were four items from the dimension of relation quality and twelve items the dimensions of well-being quality that were misfit model. These indicated that the items did not really measure the latent construct desired and need to be removed or reviewed.